Clinical focus. The University of Texas at Dallas/Callier Center for Communication Disorders Doctor of Audiology Program. - Roeser RJ; Thibodeau L; Cokely C (American Journal of Audiology, 2005)
PURPOSE: The purpose of this article is to describe the history and resources of the doctor of audiology (AuD) program at the University of Texas at Dallas (UTD)/Callier Center for Communication Disorders, as well as to provide an overview of the program. METHOD: Data from 1999, when the AuD program was approved by the Texas Higher Education Coordinating Program, to the present were reviewed. CONCLUSIONS: The UTD/Callier Center AuD program includes more than 40 faculty members, spans 3 campuses, and has 8 research laboratories. Total enrollment is 32 students (8 students are admitted each year for the 4-year program). Students have access to extensive resources and learning opportunities. The clinical and research programs at the UTD/Callier Center are actively involved in providing high-quality, in-depth education to future doctors of audiology.